Psychoeducation in Students of Jeron Elementary School with Behavioral Disorders Using the Application of Token-U Technique - ROSALINDA, Ela (Community Services: Sustainability Development, 2025)
This study aims to analyze the application of the Economic-U Token technique in psychoeducation in students of SDN Jeron Boyolali who experience behavioral disorders. This study uses an experimental method with a pretest-posttest design to assess changes in student behavior after the application of the U-Economy Token technique. The subject of the study was a student of SDN Jeron Boyolali, who was identified as having a pretest-posttest design to assess changes in student behavior after the application of the U-Economy Token technique. The subject of the study was a student of SDN, Jeron Boyolali, who was identified as having a behavioral disorder. The results of the study show that the application of the Economy-U Token technique is effective in increasing students' positive behavior, reducing the frequency of aggressive and destructive behavior, and improving social interaction between students, classmates and teachers. In addition, students showed improvement in their ability to follow the rules and increased engagement in learning activities. However, this study also found challenges in terms of the consistency of application and students' dependence on external factors that can affect the sustainability of behavior change in the long term. This study concludes that the Economy-U Token technique can be one of the effective methods in psychoeducation to deal with behavioral disorders in elementary school students. This research provides important insights for educators and professionals in the field of educational psychology to integrate positive reinforcement techniques in an effort to improve student behavior and support their social-emotional development.